Changes in knee extension and flexion maximal and rapid torque characteristics during a collegiate women's soccer season - Akehi, K.; Palmer, T. B.; Conchola, E. C.; Thompson, B. J.; Kasl, A.; Bice, M.; Unruh, S. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to assess the changes in maximal and rapid torque capacities of the knee extensor and flexor muscles over the course of a competitive season in NCAA Division II women's soccer players. Eighteen female soccer athletes performed 2 maximal voluntary isometric contractions (MVICs) of the knee extensor and flexor muscles before, during, and at the end of the competitive season. Peak torque (PT) and rate of torque development (RTD) at 50 (RTD50), 200 (RTD200), and 100-200 (RTD100-200) milliseconds were extracted from each MVIC for both legs. The rapid (RTD50) to maximal force ratio (RTD:PT), hamstring-to-quadriceps (H:Q) strength ratio, and bilateral strength differences were also calculated. Results indicated that PT, RTD50, and RTD200 decreased 11-21% from the preseason to the midseason for the knee extensors (p < 0.02) and RTD50 increased approximately 11% from the midseason to the end of season for the knee flexors (p < 0.01). Rate of torque development-to-PT ratios for the knee extensors and flexors increased 12-25% at the end of the season (p < 0.05). Also, H:Q strength ratios using PT, RTD50, and RTD200 increased 12.5-24% after the season started (p = 0.001-0.04). There were no bilateral strength differences (dominant vs. non-dominant limbs) across the season (p > 0.05). These findings suggest that participation in a soccer season can change maximal and rapid torque production of the knee extensors and flexors. Coaches and clinicians should consider incorporating a season-long strength training and maintenance plan for soccer players with the aim to improve athletic performance and minimize the risk of musculoskeletal injuries to the lower extremities.